Impact of Risk Management on Financial Performance : Moderating Role of GCG Self-Assessment - Antika Yusnia; Mohamad Hasanudin; Kenneth Pinandhito (International Journal of Economics, Commerce, and Management, 2025)
This study uses GCG self-assessment as a moderating variable to investigate how risk management, in particular operational, credit, and liquidity risk, affects financial performance. utilizing secondary and quantitative data from the websites of the Financial Services Authority (OJK) and each Rural Bank (BPR) for the 2019–2023 timeframe. Purposive sampling was the approach utilized to acquire the study's sample. There are 17 rural banks included in the sample size. The Structural Equation Modeling (SEM) approach and the SmartPLS 3.2.9 analysis tool are used in research data processing. The findings of the study demonstrate that operational risk significantly and negatively impacts financial performance. Liquidity risk has a positive but not significant effect on financial performance, while credit risk has a negative impact. This study also discovered that while GCG self-assessment was able to moderate the association between credit risk and financial performance, it was unable to moderate the relationship between financial performance and operational risk or liquidity risk.